2017
DOI: 10.1038/s41598-017-01204-6
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy and Clinical Parameters Favoring the Presence of Diabetic Nephropathy could Predict Renal Outcome in Patients with Diabetic Kidney Disease

Abstract: Diabetes duration, diabetic retinopathy (DR), and a diagnostic model have been proposed as clinical parameters favoring the presence of diabetic nephropathy (DN) in biopsied patients with diabetic kidney disease. DN, compared with non-diabetic renal disease, had poorer renal outcomes. We tested whether these clinical parameters favoring DN are associated with poorer renal outcomes in non-biopsied patients. In this study, 1330 patients with type 2 diabetes and chronic kidney disease stages 1–4 were included and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
5
27
0
1
Order By: Relevance
“…Another issue that should be considered is the coexistence of diabetic retinopathy and DKD [37]. We recently found that the -1082A>G polymorphism is associated with diabetic retinopathy in type 2 diabetic patients (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Another issue that should be considered is the coexistence of diabetic retinopathy and DKD [37]. We recently found that the -1082A>G polymorphism is associated with diabetic retinopathy in type 2 diabetic patients (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Selected by lasso regression model,diabetic nephropathy(DN) may be a signi cant risk factor of postoperative NVG onset.As previously reported,diabetic retionopathy has been associated with a faster decline in the estimated glomerular ltration rate(eGFR) among the general population and the elderly population with or without diabetes [21][22].Chi-Chih Hung [23] and his colleagues have also found that diabetic retinopathy was signi cantly associated with an increased risk for end-stage renal disease.In our study, DN could also be considered as an important risk factor for NVG onset to some extent.…”
Section: Discussionmentioning
confidence: 72%
“…It could not be overemphasized that VEGF is a pivotal angiogenic factor induced by retinal ischemia,and the vitreous level of VEGF at the time of vitrectomy is associated with a signi cant risk of both the postoperative progression of PDR and the occurrence of postoperative complications [23][24].Anti-VEGF therapy has been validated to be effective in promoting the absorption of VH and visual rehabilitation.So in the management of PDR, it is important to control ischemic stimuli primarily by anti-VEGF therapy as a preoperative therapy,which is combined with other methods,such as panretinal photocoagulation and vitrectomy.However,Wakabayashi et al [25] did not nd signi cant relation between vitreous VEGF levels at the time of vitrectomy and postoperative late complications due to persistent overproduction of VEGF after surgery,which reminded us that it is essential to continuously detect and suppress the level of VEGF.We speculated that persistent secretion of VEGF might ascribe to underlying comorbidities that might exacerbate retinal ischemia.…”
Section: Discussionmentioning
confidence: 99%